The Influence of Training, Communication and Supervision on Employee Occupational Safety At the Dept Plant Job Site Kaltim Prima Coal PT . Antareja Mahada Makmur, East Kalimantan - Ridhani Pizi; Harianto Respati; Mokhamad Natsir (Dinasti International Journal of Digital Business Management, 2026)
The objectives of this study are; 1) to analyze the effect of job training on employee safety; 2) to analyze the effect of organizational communication on employee safety; 3) to analyze the effect of management supervision on employee safety; 4) to identify the most dominant variables in influencing job safety. This study uses a quantitative approach with multiple linear regression analysis method. The population in this study were all employees of the Plant Department of PT. Antareja Mahada Makmur. The sampling technique used purposive sampling with a total of 57 respondents. Data collection was carried out through distributing questionnaires and supporting interviews, while data analysis included validity tests, reliability tests, classical assumptions, and regression tests. The results of this study are; 1) Job training has a positive and significant effect on job safety; 2) Organizational communication has a positive and significant effect on job safety; 3) Management supervision has a positive and significant effect on job safety; 4) Among the three variables, job training is the most dominant variable in improving employee safety. The implications of this study confirm that increasing the effectiveness of training programs, accompanied by open K3 communication and consistent field supervision, can strengthen the work safety culture in the mining sector. Therefore, companies are advised to make continuous training a top priority in their occupational health and safety policies